Molecular detection of Rickettsiales and a potential novel Ehrlichia species closely related to Ehrlichia chaffeensis in ticks (Acari: Ixodidae) from Shaanxi Province, China, in 2022 to 2023 - Zhang, Xue; Lv, Wen; Teng, Zhongqiu; Zhao, Na; Zhou, Yue; Ma, Di; Ma, Lin; Cheng, Yuqing; Wei, Jianjun; He, Jia; Ma, Wenke; Liu, Dongli; et al. (Frontiers in Microbiology, 2024)
Important tick-borne diseases include spotted fever group Rickettsia (SFGR), Anaplasma, and Ehrlichia, which cause harm to animal and human health. Ixodidae are the primary vectors of these pathogens. We aimed to analyze the prevalence and genetic diversity of SFGR, Anaplasma, and Ehrlichia species in the Ixodidae in Shaanxi Province, China. Herein, 1113 adult Ixodidae ticks were collected from domestic cattle and goats, and detected using nested PCR. A total of four Ixodidae species were collected and Ca. R. jingxinensis (20.58%, 229/1113), A. bovis (3.05%, 34/1113), A. capra (3.32%, 37/1113), A. marginale (0.18%, 2/1113), E. sp. Yonaguni138 (0.18%, 2/1113), and a potent novel Ehrlichia species named E. sp. Baoji96 (0.09%, 1/1113) were detected. A. marginale was detected for the first time in Rhipicephalus microplus. E. sp. Baoji96 was closely related to E. chaffeensis and was first identified in Haemaphysalis longicornis. In addition, co-infection with two Rickettsiales pathogens within an individual tick was detected in 10 (1.54%) ticks. This study provides a reference for the formulation of biological control strategies for ticks and tick-borne diseases in Shaanxi Province, and could lead to an improved control effect.